Cell Penetration, Herbicidal Activity, and in‐vivo‐Toxicity of Oligo‐Arginine Derivatives and of Novel Guanidinium‐Rich Compounds Derived from the Biopolymer Cyanophycin. Issue 10 (10th October 2018) - Grogg, Marcel; Hilvert, Donald; Ebert, Marc‐Olivier; Beck, Albert K.; Seebach, Dieter; Kurth, Felix; Dittrich, Petra S.; Sparr, Christof; Wittlin, Sergio; Rottmann, Matthias; Mäser, Pascal
Abstract : Oligo‐arginines are thoroughly studied cell‐penetrating peptides (CPPs, Figures 1 and 2 ). Previous in‐vitro investigations with the octaarginine salt of the phosphonate fosmidomycin (herbicide and anti‐malaria drug) have shown a 40‐fold parasitaemia inhibition with P. falciparum, compared to fosmidomycin alone ( Figure 3 ). We have now tested this salt, as well as the corresponding phosphinate salt of the herbicide glufosinate, for herbicidal activity with whole plants by spray application, hoping for increased activities, i.e . decreased doses. However, both salts showed low herbicidal activity, indicating poor foliar uptake ( Table 1 ). Another pronounced difference between in‐vitro and in‐vivo activity was demonstrated with various cell‐penetrating octaarginine salts of fosmidomycin: intravenous injection to mice caused exitus of the animals within minutes, even at doses as low as 1.4 μmol/kg ( Table 2 ). The results show that use of CPPs for drug delivery, for instance to cancer cells and tissues, must be considered with due care. The biopolymer cyanophycin is a poly‐aspartic acid containing argininylated side chains ( Figure 4 ); its building block is the dipeptide H‐ β Asp‐ α Arg‐OH (H‐Adp‐OH). To test and compare the biological properties with those of octaarginines we synthesized Adp8 ‐derivatives ( Figure 5 ). Intravenouse injection of H‐Adp8 ‐NH2 into the tail vein of mice with doses as high as 45 μmol/kg causes no symptoms whatsoever ( Table 3 ), but H‐Adp8 ‐NH2 is not cell penetrating (HEK293 and MCF‐7 cells, Figure 6 ). On the other hand, the fluorescently labeled octamers FAM‐(Adp(OMe))8 ‐NH2 and FAM‐(Adp(NMe2 ))8 ‐NH2 with ester and amide groups in the side chains exhibit mediocre to high cell‐wall permeability ( Figure 6 ), and are toxic ( Table 3 ). Possible reasons for this behavior are discussed ( Figure 7 ) and corresponding NMR spectra are presented ( Figure 8 ). Abstract :